Cognitive Wireless Communication Networks - Hossain, Ekram; Bhargava, Vijay K. (Springer US : Imprint: Springer, 2007)
Cognitive Wireless Communication Networks provides a unified view on the state-of-the-art in what has emerged as a promising technology for maximizing the utilization of the limited radio bandwidth. With interest in this technology increasing among researchers in both academia and industry and spectrum policy makers, this book offers a wide range of information on the subject. Topics covered include the fundamental challenges and issues in designing cognitive radio systems to the information-theoretic analysis of such systems, spectrum sensing and co-existence issues, adaptive physical layer protocols and link adaptation techniques for cognitive radio, orthogonal frequency division multiple access (OFDM) and ultra wide band (UWB)-based cognitive radio, different techniques for spectrum access by distributed cognitive radio, cognitive medium access control (MAC) protocols, decentralized learning-based dynamic spectrum access methods as well as macroeconomic models for spectrum management in cognitive radio.